Konservasi In Vitro Tanaman Jeruk Besar (Citrus maxima (Burm.) Merr.) Kultivar Srinyonya Menggunakan Osmotikum dan Retardan - Iswari S Dewi; Gani Jawak; Ika Roostika; Muhammad Sabda; Bambang S Purwoko; Widiati H Adil (Jurnal AgroBiogen, 2010)
In Vitro Conservation of Pomelo (Citrus maxima (Burm.)Merr.) cv Srinyonya Using Osmoticum and Retardant.Iswari S. Dewi, Gani Jawak, Ika Roostika, M. Sabda,Bambang S. Purwoko, and Widiati H. Adil. Pomelo is anunderutilized citrus fruit with a potential for commercialization.Only some cultivars have been conserved ex situ, suchas in home yards or in botanical gardens. Such collectionsare vulnerable to biotic and abiotic hazards. The goal of theexperiment was to study the effect of osmoticum (sorbitol)and retardant (ancymidol) on in vitro growth of pomelo.Four-leaf in vitro shoots of pomelo cultivar Srinyonya wereused as plant materials. Murashige-Skoog (MS) medium wasused as the basal medium for the culture. The trial wasarranged in a completely randomized design with threereplications. The treatments consisting of MS + sorbitol (0,20, 40, and 60 g/l) and MS + ancymidol (0, 1, 3, and 5 mg/l).The results indicated that based on plant height, number ofnew leaves, and visual plant architecture, sorbitol treatmentsfrom 20-60 g/l retard the growth of the pomelo plant significantly.On the other hand, ancymidol did not inhibit thepomelo growth significantly, but it was a suitable osmoticumfor improvement of in vitro plant vigor, increasing greencolor of leaf, and increasing root initiation. Leaf senescenceof in vitro plants cultured on media containing sorbitol 40and 60 g/l began 20 week after storage. The best medium forconservation of pomelo cv Srinyonya was MS + 20 gsorbitol/l.